2003
DOI: 10.1042/cs20020192
|View full text |Cite
|
Sign up to set email alerts
|

ETA receptors mediate vasoconstriction, whereas ETB receptors clear endothelin-1 in the splanchnic and renal circulation of healthy men

Abstract: The contribution of the endothelin (ET) receptors ET(A) and ET(B) to basal vascular tone and ET-1-induced vasoconstriction in the renal and splanchnic vasculature was investigated in six healthy humans. ET-1 was infused alone and in combination with the selective ET(A) receptor antagonist BQ123 or the selective ET(B) receptor antagonist BQ788 on three different occasions. BQ123 did not affect basal arterial blood pressure, splanchnic vascular resistance (SplVR) or renal vascular resistance (RVR), but inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
8
13
0
Order By: Relevance
“…4B). These results altogether indicate that ET A , but not ET B , is the predominant vasoconstrictor ET receptor in the mouse abdominal aorta, which concurs with reports on several rat as well as human vessels (5,8,12,21,22,25).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4B). These results altogether indicate that ET A , but not ET B , is the predominant vasoconstrictor ET receptor in the mouse abdominal aorta, which concurs with reports on several rat as well as human vessels (5,8,12,21,22,25).…”
Section: Discussionsupporting
confidence: 93%
“…While ET B receptors present in the smooth muscle mediate vasoconstriction (13,14,24), those in the endothelial cell cause vasodilation via the release of endothelium-dependent relaxing factors, such as nitric oxide (NO) (12,17,23). However, it has been recently found that part of the depressor effect of ET B receptor may be related to the clearance of ET-1 in the plasma (3,5). In addition, ET A receptor has also been suggested to be functional in the endothelial cells (11,18,19).…”
mentioning
confidence: 97%
“…The ET A receptor antagonist BQ‐123 was demonstrated to lower blood pressure acutely in CIH‐treated, but not sham, rats and to prevent CIH‐induced increases in arterial pressure . Together, these results indicate that the ET A receptor is the predominant receptor mediating ET‐induced vasoconstriction, which is consistent with reports from human vessels …”
Section: Introductionsupporting
confidence: 87%
“…This receptor does not modulate the haemodynamic properties of Big ET‐2 as it is poorly converted in the pulmonary or systemic circulation in anaesthetized rabbits. This is supported by human in vivo studies done by Bohm et al . (2003), which showed that ET B functions as a clearance receptor and may modulate ET A ‐mediated vasoconstriction by altering the plasma concentration of ET‐1.…”
Section: Does Et‐2 Have a Separate Synthesis From Other Et Peptides?supporting
confidence: 78%